Upaya Pemeliharaan Fungsi Hati Melalui Skrining SGOT/SGPT pada Usia Produktif di Kelurahan Grogol - Andria Priyana; Alexander Halim Santoso; Farell Christian Gunaidi; Cristian Alexandro; Louis Anthony (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
Liver disease is an increasingly prevalent health problem among the productive-age population, primarily driven by unhealthy lifestyles, alcohol consumption, obesity, and the risk of hepatitis infection. Liver dysfunction often presents no specific symptoms in its early stages, making early detection challenging. The Community Service Program (PKM) conducted in Grogol Village aimed to raise public awareness about the importance of early liver function screening through SGOT and SGPT enzyme assessments. This activity included education on risk factors as well as on-site liver enzyme testing for participants. Among the 71 participants, 18 individuals (25.35%) had elevated SGOT levels, and 17 individuals (23.94%) showed SGPT levels exceeding normal limits. These findings highlight the importance of early liver function screening in preventing the progression to chronic liver diseases such as NAFLD or hepatitis, and in serving as an indicator of cardiometabolic risk. Therefore, routine liver enzyme testing can serve as a foundation for increasing public awareness about the importance of maintaining liver and metabolic health in a sustainable manner.